Physical scale modeling of single free head piles under lateral loading in cohesive soils - Salamanca-Medina, Edgar Leonardo; Abril-Gonzalez, Nebardo Arturo (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
This paper presents the results of the small scale modeling of free head wood piles under horizontal loading in cohesive soils, tested in order to compare the results with analytical models proposed by various authors. Characteristic Load (CLM) and P-Y Curves methods were used for the prediction of lateral deflections at the head of the piles and the method proposed by Broms for estimating the ultimate lateral load. These predictions were compared with the results of the physical modeling, obtaining a good approximation between them.